Diversification of rice (Oryza sativa L.) based cropping systems for higher productivity and benefits on dominant soil series of upper Brahmaputra valley, Asom - Singh, Dharam; Bhaskar, B.P.; Baruah, U.; Sarkar, Dipak (Annals of Agricultural Research, 2014)
On-farm field experiments on rice based cropping systems were conducted in split-split plot design during 2005 to 2007 on four dominant soil series viz., Lahangaon series (Aeric Fluvaquents), Bhogdai series (Fluvaquentic Endoaquepts), Matikhola series (Typic Endoaquepts) and Teok series (Typic Fluvaquents) of Jorhat district, Asom such as rice-fallow, rice -potato, rice -pea and ricemustard at two levels of management i.e. farmers practices (FP) and recommended package of practices (RPP). The experimental results showed that the productivity of rice-potato system under RPP was recorded rice equivalent yield (REY) of 15.66 t/ha in Lahangaon series followed by Bhogdai (13.84 t/ha) and Matikhola (11.11 t/ha), whereas, rice -pea system performed well in Teok series under flooded situation (10.1 t/ha). Thus rice -potato is most productive and remunerative cropping system under RPP over FP at all the soil series but best results were recorded at Lahangaon series.